Optimism for the Single-stage Transanal Swenson in Neonates - Wesam Mohamed; Mohamed I Elsawaf; Aly I Shalaby; Ahmed E Arafat; Mahmoud M Marei; Mohamed H Aboulfadl; Sherif N Kaddah; Gamal H El Tagy; Khaled H K. Bahaaeldin (Wolters Kluwer Medknow Publications, 2021)
Background: Hirschsprung's disease (HD) has been traditionally treated from infancy onward and different techniques have been used including Swenson, Soave, and Duhamel procedures. The purpose of this study was to evaluate the transanal Swenson's procedure for classical rectosigmoid HD in neonates. Patient and Methods: This was a prospective study in which neonates diagnosed with HD were recruited from January 2017 to December 2018. Cases with a transition zone proximal to the midsigmoid were excluded. All patients underwent a transanal Swenson's procedure in the neonatal period using a unified protocol. Intraoperative course and postoperative outcomes such as leak, pelvic abscess, soiling, perianal excoriation, stricture, enterocolitis, and constipation were evaluated and all patients were followed for at least 6 months. Results: Twenty-three patients (17 males and 6 females) underwent transanal Swenson's procedure. The mean age was 22 ± 5.7 days. Follow-up ranged from 6 to 30 months. No anastomotic leak, retraction, or prolapse was reported. Mild perianal excoriations occurred early in 9 (39%) cases and all responded to medical treatment and disappeared before 2 months postoperatively. Stricture occurred in 2 (8%) patients, enterocolitis in 3 (13%), and constipation in 3 (13%). Conclusion: Transanal Swenson's procedure is feasible and can be performed safely in neonates with rectosigmoid HD with good short-term outcomes. Proper patient selection and standard protocol following fine procedural hall-marks and details are keys for optimal results and patient satisfaction.